A Pedagogical Approach to Field Linguistics during the Coronavirus Pandemic Crisis - Thawornpat, Mayuree; Boonkuson, Surapol (Language and Linguistics, 2023)
The coronavirus pandemic 2019 has not only affected public health and the economy but also education, especially pedagogical approaches to field practicums. This article discusses the problems, and presents a process and guidelines for an appropriate pedagogical model for field linguistics during the coronavirus pandemic. This is achieved by synthesizing the academic literature and qualitative research methods, including interviews with lecturers and administrators, and a questionnaire for students at various universities in Thailand studying related pedagogical approaches to field linguistics. The results show that all universities have changed their teaching methods from classroom teaching to online teaching, using a selection of applications available on the internet. This has led to changes in field research methods, from real to virtual. While various technologies and digital media have been used in teaching and learning, the course content has remained the same.